2006
DOI: 10.4028/www.scientific.net/msf.510-511.750
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Activated Carbon Fibers by Chemical Activation Method with Hydroxides

Abstract: Activated carbon fibers were prepared from stabilized PAN-based fibers by chemical activation using hydroxides at different concentrations. The experimental data showed variations in specific surface area, microstructure, pore size distribution, and amounts of iodine adsorbed by the activated carbon fibers. Specific surface area of about 2244m2/g and iodine adsorption of 1202mg/g were obtained in the KOH 1.5M. However, the use of NaOH in the activation process rather than KOH and using the same time/ temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…6KOH + 2C → 2K + 3H 2 +2K 2 CO 3 (5) Our previous studies [16,17] showed that, in the low temperature region (<600…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…6KOH + 2C → 2K + 3H 2 +2K 2 CO 3 (5) Our previous studies [16,17] showed that, in the low temperature region (<600…”
Section: Introductionmentioning
confidence: 96%
“…It is generally produced from raw materials with high carbon content, such as petroleum coke (PC) and anthracite, by alkaline hydroxides such as NaOH and KOH activation. In most cases, KOH is chosen as the activation agent because it exhibits superior activation activity than NaOH [5], yielding an AC with a higher specific surface area and a more abundant pore structure. In this process, a large amount of KOH, i.e., a high ratio of KOH to the carbonaceous feedstock, has to be used, which leads to high production costs, reactor corrosion and safety risks [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon fiber, a relatively new adsorbent, offers wonderful adsorption properties, such as faster adsorption rate, longer life and lower pressure drop, in comparison with traditional granular activated carbon. Therefore, it is widely used in separation of gases, recovery of solvents, catalyst support and removal of organic pollutants from drinking water [5,6]. The most widely used precursors for activated carbon fibers are rayon, pitch and polyacrylonitrile (PAN) fibers.…”
Section: Properties Of Electrospun Polyacrylonitrile Membranes and Chemically-activated Carbon Nanofibersmentioning
confidence: 99%